2020
DOI: 10.1037/pha0000297
|View full text |Cite
|
Sign up to set email alerts
|

BDNF association study with obsessive–compulsive disorder, its clinical characteristics, and response to fluvoxamine-treatment in Iranian patients.

Abstract: Obsessive–compulsive disorder (OCD) is a chronic neuropsychiatric disorder with complex genetic inheritance. Findings suggest a role for brain-derived neurotrophic factor (BDNF) in OCD, but reports are limited. Here we studied the association of BDNF polymorphisms rs6265 and rs2883187 with OCD and its clinical characteristics in Iranian patients as well as the fluvoxamine-treatment outcome of OCD patients. Iranian OCD patients who were diagnosed according to DSM–IV–TR entered the study. DNAs were extracted fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 51 publications
(71 reference statements)
1
9
0
Order By: Relevance
“…Pharmacogenetic evaluations of BDNF polymorphisms with treatment response in OCD have been scarce. However, our results, which indicate an absence of overall impact on the efficacy of SSRI treatment are in agreement with those of four previous association studies on BDNF variants among patients with OCD [8][9][10][11] and in a genome-wide association study of treatment response among 804 patients with OCD. 20 Real et al 11 carried out a single-marker and haplotype association study of eight BDNF SNPs on a sample of 123 Spanish Caucasian OCD patients treated with fluoxetine, fluvoxamine, or clomipramine for 12 weeks.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Pharmacogenetic evaluations of BDNF polymorphisms with treatment response in OCD have been scarce. However, our results, which indicate an absence of overall impact on the efficacy of SSRI treatment are in agreement with those of four previous association studies on BDNF variants among patients with OCD [8][9][10][11] and in a genome-wide association study of treatment response among 804 patients with OCD. 20 Real et al 11 carried out a single-marker and haplotype association study of eight BDNF SNPs on a sample of 123 Spanish Caucasian OCD patients treated with fluoxetine, fluvoxamine, or clomipramine for 12 weeks.…”
Section: Discussionsupporting
confidence: 93%
“…9 Similarly, among 94 Iranian patients, none of the two BDNF SNPs studied (rs6265, rs2883187) nor their haplotypes were associated with response to fluvoxamine after 12 weeks. 10 The importance of clinical OCD symptom subtypes has been underlined in recent years. Thus, not taking these dimensions into account could be a confounding factor in the interpretation of studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with few studies in Iran, e.g. a study by Abdol-Hosseinzadeh et al [44], the present study aimed to investigate the role of Val-66Met polymorphism in BDNF gene in OCD among the Iranian population.…”
Section: O Highlightsmentioning
confidence: 89%
“…A recent meta-analysis found that brain-derived neurotrophic factor (BDNF) is significantly reduced in individuals with OCD (Suliman et al, 2013). A significant association was detected between BDNF polymorphism rs2883187 and OCD (Abdolhosseinzadeh et al, 2019), and Hall et al (2003) showed a strong association between BDNF gene sequence variants, including the Val66Met variation, and OCD. Subsequent studies also showed that the Val66-Met BDNF gene variant is a risk allele for development of OCD, possibly in a sex-specific manner (Hemmings et al, 2008;Katerberg et al, 2009).…”
Section: Psychopharmacology Of Ocd: a Preclinical Roadmapmentioning
confidence: 99%